Promoting Change through Action Research
VI, 250 p.
Keywords: “Bringing a different world into existence – Action Research as a trigger for innovations” was the overarching theme and vision of the international CARN Conference 2011 in Vienna. The chapters in this book are drawn mainly from conference contributions. The authors share practical knowledge which has arisen from their work, and reflect on development processes in schools, in teacher education and professional development, social work, social peda¬gogy, health care and community development. This book offers what some critics believe has been missing in recent action research literature, namely first person accounts of action researchers who endeavour to change working conditions and social relations in their environment through the conduct of action research. This book is also distinguished by assembling contributions from people who are linking action research to a broad diversity of differing contexts, and who are exploring topics or issues across various applications of action research.